Cross-Market Investor Sentiment in Commodity Exchange-Traded Funds - Hsiu-Lang Chen (Credit and Capital Markets – Kredit und Kapital, 2015)
This study shows how the investor sentiment in the stock market affects prices of commodity exchange-traded funds (ETFs). The study provides quantitative evidence that the tracking errors of commodity ETFs differ in the bullish versus the bearish stock market, and the aggregate tracking error of commodity ETFs is sensitive to the well-known sentiment measures. The study exploits a profitable trading strategy based on investor sentiment in the stock market and commodity market. The sentiment-driven demand for commodity ETFs could exist even after consideration of trading costs, and it is a short-term phenomenon. This unique evidence indicates investor sentiment affects asset valuation across markets. – – Anleger-Sentiment bei Rohstoff-Exchange-Traded-Funds auf verschiedenen Märkten Diese Studie zeigt, wie sich Sentiment-Faktoren am Aktienmarkt auf die Preise von Rohstoff-Exchange-Traded-Funds (ETFs) auswirken. Die Studie liefert quantitative Evidenz dafür, dass die Tracking Errors von Rohstoff-ETFs sich in aufwärts und abwärts tendierenden Aktienmärkten unterscheiden und dass der aggregierte Tracking Error von Rohstoff-ETFs deutlich mit den verbreiteten Sentiment-Indikatoren zusammenhängt. Sie verwendet eine profitable Handelsstrategie basierend auf dem Anleger-Sentiment in Aktien- und Rohstoffmärkten. Die vom Sentiment getriebene Nachfrage nach Rohstoff-ETFs existiert auch unter Berücksichtigung von Transaktionskosten und stellt ein kurzzeitiges Phänomen dar. Wie die Ergebnisse der Studie zeigen, wirkt sich das Sentiment auch auf Preisbildung auf verschiedenen Märkten aus.
Keywords: G10; G23; 330; Investor Sentiment; Tracking Errors; Commodity ETFs